Realitas kesejahteraan individu dalam pengaplikasian teori dimensi keagamaan Redorick Ninian Smart - Husna, Faidatul; Soleh, Achmad Khudori (Maliki Interdisciplinary Journal, 2024)
The writing of this article was motivated by the researcher’s curiosity in studying the relationship between theories from a psychological and religious perspective. This research aims to conduct a detailed study of the seven religious dimensions according to Redorick Ninian Smart, which include ritual, emotional, mythic, ethical, social and material dimensions, especially in influencing the welfare conditions of individuals who apply these religious dimensions well. The analysis shows that the results of applying the religious dimension well are able to improve individual welfare conditions for the better. This is proven when individuals are able to use the religious dimension as the main shield in an effort to control themselves, feel inner prosperity, achieve prosperity in life, and realize life goals.